Utilization of face masks and ladle furnace slag in concrete: Insights from experimental study - Md. Tarif Aziz; Md. Sheikh Sohrab Hossain; Md. Abul Hasan; Mohammad Arif Mohiuddin (Cleaner Engineering and Technology, 2023)
Since Covid-19 outbreak, billions of single used face masks (SUFM) are being used which pose a great concern in terms of environmental pollution – SUFM do not disintegrate easily. Reuse of used masks in concrete could be a pollution mitigating option. In this study, a unique series of testing program, incorporating pieced SUFM and powdered ladle furnace slag (LFS) in concrete, was considered. To prepare concretes, SUFM fibers were added as a volumetric replacement and LFS powder was added as supplementary cementitious material (SCM). Two different percentages (0.1% and 0.2%) and sizes (small: 5 × 20 mm and large: 5 × 40 mm) of SUFM fibers were used, and two different percentages (5% and 15%) of LFS were incorporated (along with SUFM) in concrete. Subsequently, control concretes, SUFM blended concretes, and SUFM-LFS blended concretes were prepared to carry out compressive strength tests, flexural strength tests, and sorptivity (i.e., capillary water absorption) tests. For SUFM blended concretes, the compressive strength and flexural strength results are found to be decreasing: 0.1% larger sized SUFM shows less decrease in strength (15.2% for compressive and 2.1% for flexure) when compared with control concretes. In the case of SUFM-LFS blended concretes, compressive strength is in decreasing trend whereas flexural strength is found to be increased with a peak increment of 8.3% compared to control concrete. In the case of sorptivity, higher amount of SUFM inclusion shows increased water absorption by concrete while larger amount of LFS inclusion produces concretes having less affinity to water. In general, larger sized SUFM blended concretes provide better concrete if compared with other blended samples.